Tax Revenue Downturns : Anatomy and Links to Imports - Li, Kun (IMF Working Papers; Working Paper ;, 2010)
We study historical tax revenue downturn episodes-where tax revenue-to-GDP ratios decline sharply-and explore the link between tax revenues and imports. We document that downturn episodes of at least 1 percentage point of GDP in one year are common. The tax types that account for these episodes are different in advanced, emerging and developing, and oil producing countries. We find that tax revenue downturns and import contractions have a statistically significant link. Finally, we show that changes in imports are a statistically significant determinant of changes in tax revenues even when controlling for changes in the output gap and in the terms of trade.